The Value of Patience in Surah Al-Insyirah Verses 1-4: Application to Students from the Hedonistic Attitude in the 21st Century of the Tahlili Perspektive Interpertation - Heru Chakra Setiawan; Indah Fatmawati (Proceeding International Conference on Religion, Science and Education, 2023)
The various challenges faced by students in the 21st century are of course increasingly complex, with the development of technology and easy access to information making it easier for students to access any information. Not infrequently, every information contained contains advertisements that lead to a hedonic attitude that is only concerned with luxury. The current generation, known as generation Z, is considered to be easily influenced by the hedonistic attitude offered, it will be easier to cause frustration for students if they are unable to fulfill it. So that in responding to this in the 21st century it must be accompanied by high knowledge, critical thinking, innovative and creative ability as well as faith and piety. Furthermore, from the data that the researchers found on 26 students majoring in Sharia Economic Law at IAI Riyadlotul Mujahidin, it was found that as many as 80% had a hedonic attitude, such as not wanting to be left behind to have the latest smartphone without considering their needs and functions, even to the point that some were involved in debt. Students follow the style of hedonism because they lack the value of patience in themselves. This study aims to analyze how the application of the value of patience contained in Al-Insyirah verses 1-4 to students majoring in Sharia Economic Law at IAI Riyadlotul Mujahidin is seen from the presentation of both classical and contemporary interpretations. In this study, researchers used a descriptive analysis method through field study techniques. The data is then analyzed with the perspective of tahlili interpretation. One of the applications of the value of patience from the interpretation of tahlili is those who are illuminated by light in their chests or guidance from Allah, and promises to be elevated in rank and position by Allah SWT whose implementation is very necessary for students in facing challenges in the 21st century.